2021
DOI: 10.3390/polym13162718
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Bone Cell Formation with Poly-ε-Caprolactone/Bioceramic 3D Porous Scaffolds

Abstract: This study applied poly-ε-caprolactone (PCL), a biomedical ceramic powder as an additive (nano-hydroxyapatite (nHA) or β-tricalcium diphosphate (β-TCP)), and sodium chloride (NaCl) and ammonium bicarbonate ((NH4)HCO3) as porogens; these stuffs were used as scaffold materials. An improved solvent-casting/particulate-leaching method was utilized to fabricate 3D porous scaffolds. In this study we examined the physical properties (elastic modulus, porosity, and contact angle) and degradation properties (weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…1 B. The compression modulus of porous PEEK scaffolds in the X-axis and Z-axis directions were 376 ± 17 MPa and 407 ± 25 MPa, respectively, which were similar to the modulus of cancellous bone (0.1–4.5 GPa [ 30 ]). The compression modulus of the PEEK blocks was 1183 ± 74 MPa.…”
Section: Resultsmentioning
confidence: 71%
“…1 B. The compression modulus of porous PEEK scaffolds in the X-axis and Z-axis directions were 376 ± 17 MPa and 407 ± 25 MPa, respectively, which were similar to the modulus of cancellous bone (0.1–4.5 GPa [ 30 ]). The compression modulus of the PEEK blocks was 1183 ± 74 MPa.…”
Section: Resultsmentioning
confidence: 71%
“…Cell viability increased proportionally with the addition of β-TCP, a finding similar to results by Bruyas et al who proposed that increased β-TCP could increase surface roughness which facilitates cell growth [ 46 ]. Juan et al demonstrated that MG-63 cells cultured with PCL/β-TCP had better cell proliferation and ALPase activity compared to PCL/HAP and PCL/HAP/β-TCP [ 51 ]. Bruyas et al and Shim et al have also shown that the addition of β-TCP composite could induce cellular alkaline phosphatase secretion and mineralization [ 39 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its low biological activity, hydrophobicity and poor mechanical properties limit its application in bone tissue engineering [ 72 , 73 ]. In order to improve the mechanical properties of PCL, Juan et al added n-HAp to the PCL matrix to form a three-dimensional porous composite scaffold with an elastic modulus of 0.401–1.005 GPa, within the range of elastic modulus of human cancellous bone (0.1– 4.5 GPa) [ 74 , 75 ]. The degradation rate of the bone tissue engineering scaffold should match the bone formation rate [ 76 ].…”
Section: N-hap Composite Scaffolds For Bone Repairmentioning
confidence: 99%